Bébédjia (sud du Tchad), un espace sous pression - Lieugomg Médard; Sama Ozias (VertigO, 2007)
Bebedjia, situated in the southernmost part of Chad, has a favourable climate conduisive to agro-pastoral activities. This natural environment attracts nomadic rearers from the sahelian/Saharan zones of the North which are being threatened by bad climatic conditions (recurrent droughts such as those of 1973-1975 and 1983-1985) as well as political and military instability. Forced to settle in this region and to practice agriculture in addition to their traditional activities, these nomadic rearers find themselves opposed to indigenous farmers within the context of land conflicts which are now gaining momentum due to pressure on agro-pastoral space exacerbated by the Doba Oil Projet. Instead of settling the conflicts in a friendly manner, traditional and public authorities encourage and instrumentalise them.